Being young and Coloured in Ghost Town - May, Lian Cain (Rhodes University, 2026)
‘Coloured identity’ is a category invented by the Apartheid regime that became a culture by those who self-identify as Coloured (Tewolde, 2006). ‘Colouredness’ on the other hand can be understood as the fluidity of the identity and the making of the identity throughout history (Hoffmeester, 2018). This study examines the ways in which Colouredness and the Coloured identity is understood and expressed by the youth in small town, Irving Heights/Ghost Town, Makhanda in the Eastern Cape, South Africa. The study draws from interviews with seven young self-identifying Coloured South Africans that have lived or are still live in Ghost Town. The study finds that youth in Ghost Town express Colouredness through language and the specific manner in which they speak Afrikaans, their accents and dialect. The manner in which Afrikaans is spoken across provinces in South Africa, and in neighboring countries such as Namibia, differs. While all the participants grew up speaking Afrikaans as a first language, they express that theirs is “kitchen Afrikaans” compared to “suiwer” Afrikaans which is spoken by white Afrikaans speakers. It is also the case that when Coloured youth speak what is regarded as “suiwer” (pure) Afrikaans, they are mocked for trying to be better than other Coloured people. Importantly, interviews reveal that Colouredness is expressed and understood as a “culture” that is tangible and intangible, through food, religion, sport and aesthetics, among other things. While some participants trace their Coloured heritage through the Cape Malay, Khoi and San, their sense of “culture” is embedded in the value system that is described to be that of a closeness which instilled values shaping one’s outlook on life. Living in the small Coloured community such as Ghost Town, Coloured people create spaces to co-exist and further express their Colouredness. These spaces of community include churches and sporting activities. The smallness of the town and the area is central to the value system that the participants speak about, and how this allows for varied expressions that include sexuality – such as queerness. Ultimately, this thesis contributes to the literature that traces the contours, ruptures and continuities in how Colouredness is understood and expressed in democratic South Africa.
Colouredness in a small-town
Keywords: Uncatalogued